Analysis of Risk Management on SMEs in Padang: Case Study Optic Ihsan - Septrizarty, Rika; Maliha, Dabitha Wise (STIA Adabiah, 2024)
The recession that shook the world due to Covid 19 has not ended. This situation hurts almost all SMEs, including Optic Ihsan located in Padang City, West Sumatra, vulnerable to natural disasters. Revenue that has continued to decline since the pandemic until the end of 2024 is a strong reason to conduct a risk management analysis for the continuity of the store in the future, facing the recession 2025 which is expected to peak in 2026 and end in 2027. The purpose of this study is to analyze the possible risks that exist in Ihsan Optic using ISO 31000. The research method used is qualitative. Data collection was carried out by observation and in-depth interviews. The results of this study obtained 10 possible risks that occurred, consisting of 3 High Risk, 6 Medium Risk, and 1 Low Risk. It is recommended to increase online store activities and maintain and improve service and quality through good quality management